2015
DOI: 10.1007/s11051-015-3134-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional group modification on the thermal properties of nano-carbon clusters

Abstract: In this paper, the thermal properties including thermal stability, thermal decomposition activation energy and the thermal enthalpy of nano-carbon clusters (NCCs, including fullerene[60](C 60 , with a diameter of 0.71 nm), multi-walled carbon nanotubes(MWCNTs, with a diameter of 10-30 nm and a length of 1-2 lm), single-walled carbon nanotubes (SWCNTs, with a diameter of *2 nm and a length of 5-15 lm), ligands of NCC-based terpyridine (NCC-tpy), and NCC-based ruthenium complexes (NCC-tpyRuCl 3 ) were systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It was shown that the decomposition of supported compounds depends on the support nature and can be delayed or enhanced compared with the bulk compounds [36,37]. On the other hand, the stability of CNMs to degradation can be changed in the presence of metal-containing compounds [38,39]. So the selection of the appropriate metal precursor and mode of thermal treatment of nanocomposite is required for the successful synthesis of CNMs with supported metal oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the decomposition of supported compounds depends on the support nature and can be delayed or enhanced compared with the bulk compounds [36,37]. On the other hand, the stability of CNMs to degradation can be changed in the presence of metal-containing compounds [38,39]. So the selection of the appropriate metal precursor and mode of thermal treatment of nanocomposite is required for the successful synthesis of CNMs with supported metal oxide nanoparticles.…”
Section: Introductionmentioning
confidence: 99%